Decreasing Frequency of Osteonecrosis of the Jaw in Cancer and Myeloma Patients Treated with Bisphosphonates: The Experience of the Oncology Network of Piedmont and Aosta Valley (North-Western Italy). (27th February 2013) - Fusco, Vittorio; Galassi, Claudia; Berruti, Alfredo; Ortega, Cinzia; Ciuffreda, Libero; Scoletta, Matteo; Goia, Franco; Migliario, Mario; Baraldi, Anna; Boccadoro, Mario; Loidoris, Anastasios; Bertetto, Oscar
Abstract : Background . Data concerning frequency of Osteonecrosis of Jaws (ONJ) are mostly based on single center experiences. Patients and Methods . Since 2005 a multidisciplinary study group collected data of cases of ONJ in patients treated with Bisphosphonates (BP) and observed in oncology and hematology centers of a regional network. Results . By December 2008, 221 cases were registered. We report details of 200 cases, identified after cross-checking reports from centres of medical oncology, haematology, and oral care. Primary neoplasm was breast cancer (39%), myeloma (32%), prostate cancer (16%), and other types of cancer (8%). In about 50% of the cases a history of dental extraction was present. Zoledronic acid was administered (alone or with other BP) to 178 patients (89%). Median time from first infusion to ONJ diagnosis was 21.0 (zoledronic acid only) and 39.0 months (pamidronate only). The number of ONJ cases per year was 3 in 2003, 21 in 2004, 58 in 2005, 60 in 2006, 37 in 2007, and 21 in 2008. Conclusion . The number of new ONJ cases in cancer and myeloma patients increased until 2006 and then reduced. The possible reasons of this trend (introduction of zoledronic acid; increase of ONJ awareness; diffusion of preventive dental measures; late modifications of BP prescription) are herein discussed.